Risk Factors for Coughing in Dogs with Naturally Acquired Myxomatous Mitral Valve Disease. (9th February 2013) - Ferasin, L.; Crews, L.; Biller, D.S.; Lamb, K.E.; Borgarelli, M.
<x xml:space="preserve">Abstract</x> Background Cough often is reported as the primary clinical sign of congestive heart failure (CHF) in dogs with chronic degenerative myxomatous mitral valve disease (MMVD). Concurrent airway disease and compression of the left mainstem bronchus by a large left atrium also have been proposed as potential causes of coughing in these patients. Objectives To investigate the association between the presence of coughing and different potential causes of cough, including CHF, abnormal radiographic airway pattern, and cardiomegaly in dogs affected by naturally acquired MMVD. Animals Two hundred six client‐owned dogs. Methods Retrospective analysis performed on medical records of dogs affected by MMVD that underwent full cardiac evaluation, including echocardiographic examination and thoracic radiography. Results Univariate analyses showed that CHF is not a predictor of coughing (OR = 1.369; 0.723, 2.594), whereas abnormal radiographic airway pattern (OR = 3.650; 2.051, 6.496) and increased left atrial size observed radiographically (OR = 3.637; 1.904, 6.950) or echocardiographically (OR = 2.553; 1.436, 4.539) were significantly associated with coughing in dogs with MMVD. The same risk factors were significant in multivariate analyses. Conclusions and Clinical Importance This study indicates that CHF is not significantly associated with coughing in dogs with MMVD. Instead, abnormal radiographic airway pattern and left atrial enlargement are associated with coughing in these patients. This important finding should be taken into account when considering diagnosis and clinical management of CHF in these dogs.